Biogas Production Depending on the Substrate Used: A Review and Evaluation Study—European Examples - Katarzyna Ignatowicz; Gabriel Filipczak; Barbara Dybek; Grzegorz Wałowski (Energies, 2023)
Biogas production is the most important and promising alternative for replacing fossil fuels in an environmentally friendly manner. Along with the many renewable energy sources available, biogas production occupies an irreplaceable position due to the undeniable availability of biomass and the need to manage agro-commercial waste. The article reviews the current state of technology used in the production of biogas for selected European examples in terms of methane fermentation efficiency and actual energy production. The novelty of the article is its description of innovative trends that have great potential to play an important role in this field in the near future. The development of the biogas industry in Europe is evident, although the dynamics vary from country to country. Different models are presented, which are based on the different types of feedstock used for biogas production and the proportion of substrates used in co-digesters. Of course, Germany is the undisputed pioneer in the use of this renewable energy source. Nevertheless, the efforts to improve energy self-reliance and environmental impacts are reflected in the growing number of operational biogas plants in other European countries, which provides hope for rapid progress toward the complete abolition of the conventional exploitation of fossil fuels.